Antenatal spectrum of CHARGE syndrome in 40 fetuses with CHD7 mutations. Issue 11 (28th September 2012) - Legendre, Marine; Gonzales, Marie; Goudefroye, Géraldine; Bilan, Frédéric; Parisot, Pauline; Perez, Marie-José; Bonnière, Maryse; Bessières, Bettina; Martinovic, Jelena; Delezoide, Anne-Lise; Jossic, Frédérique; Fallet-Bianco, Catherine; et al.
Abstract : Background: CHARGE syndrome is a rare, usually sporadic disorder of multiple congenital anomalies ascribed to a CHD7 gene mutation in 60% of cases. Although the syndrome is well characterised in children, only one series of 10 fetuses with CHARGE syndrome has been reported to date. Therefore, we performed a detailed clinicopathological survey in our series of fetuses with CHD7 mutations, now extended to 40 cases. CHARGE syndrome is increasingly diagnosed antenatally, but remains challenging in many instances. Method: Here we report a retrospective study of 40 cases of CHARGE syndrome with a CHD7 mutation, including 10 previously reported fetuses, in which fetal or neonatal clinical, radiological and histopathological examinations were performed. Results: Conversely to postnatal studies, the proportion of males is high in our series (male to female ratio 2.6:1) suggesting a greater severity in males. Features almost constant in fetuses were external ear anomalies, arhinencephaly and semicircular canal agenesis, while intrauterine growth retardation was never observed. Finally, except for one, all other mutations identified in our antenatal series were truncating, suggesting a possible phenotype–genotype correlation. Conclusions: Clinical analysis allowed us to refine the clinical description of CHARGE syndrome in fetuses, describe some novel features and set up diagnostic criteria in order to help the diagnosis of CHARGE syndrome after termination of pregnancies following the detection of severe malformations.